A STUDY ON CUSTOMER SATISFACTION ON INTERNET BANKING - KANAGARAJU, Dr.P.; BALAMURUGAN, G. (The journal of contemporary issues in business and government, 2021)
The development of e-banking in each country is dependent on the speed of internet access, the features of new online banking, and the frequency of e-banking usage. In the banking industry, e-banking is formed when there is a combination between the information technology and the functions of banks and financial institutions. Internet banking was first introduced in Malaysia in June 2000 when Bank Negara Malaysia gave permission to the local banks to offer Internet banking services. To satisfy customer’s need, many types of products and services were provided by the banks through Internet banking websites.